2015
DOI: 10.1002/zaac.201500550
|View full text |Cite
|
Sign up to set email alerts
|

1‐(Furan‐2‐ylmethyl)‐1H‐tetrazole and its Copper(II) Complexes

Abstract: 1-(Furan-2-ylmethyl)-1H-tetrazole (fmt), prepared by heterocyclization of furfurylamine with triethyl orthoformate and sodium azide, was found to react with copper(II) perchlorate, nitrate, and bromide giving complexes [Cu(fmt) 4 (H 2 O) 2 ](ClO 4 ) 2 , [Cu(fmt) 3 (NO 3 ) 2 (H 2 O)], and [Cu 2 (fmt) 4 Br 4 ], respectively. The obtained crystalline complexes and fmt were characterized by X-ray diffraction, thermal analyses, and IR spectroscopy. In the complexes, fmt acts as a monodentate ligand coordinated via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As for metal-involving bonds, the Cu(1)−Br(2) length of the terminal bromide ion (see Table 3 ) is about 0.06 Å shorter than the Cu(1)−Br(1) distance (2.3687 (6) vs. 2.4302 (4) Å); the Cu(1)−Br(1) I bond length of the µ-bridging Br ion is instead appreciably longer at 2.7600 (5), about 0.33 Å longer than the terminal Cu−Br bond. This value is higher than the reported average for similar compounds (2.59 Å) but fits within the reported range (2.37–3.06 Å) [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Similar considerations can apply to the Cu−N(1) and Cu−N(3) distances: respectively, 2.017 (2) and 2.042 (3) Å (mean: 2.00, range: 1.97–2.09 Å).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…As for metal-involving bonds, the Cu(1)−Br(2) length of the terminal bromide ion (see Table 3 ) is about 0.06 Å shorter than the Cu(1)−Br(1) distance (2.3687 (6) vs. 2.4302 (4) Å); the Cu(1)−Br(1) I bond length of the µ-bridging Br ion is instead appreciably longer at 2.7600 (5), about 0.33 Å longer than the terminal Cu−Br bond. This value is higher than the reported average for similar compounds (2.59 Å) but fits within the reported range (2.37–3.06 Å) [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Similar considerations can apply to the Cu−N(1) and Cu−N(3) distances: respectively, 2.017 (2) and 2.042 (3) Å (mean: 2.00, range: 1.97–2.09 Å).…”
Section: Resultssupporting
confidence: 88%
“…The crystal structure investigation revealed that, in the solid state, the compound exists as a dimer of formula [Cu(L OHex )Br(μ-Br)] 2 , with the Br(1) ions binding two symmetry-related units to each other. To the best of our knowledge, this complex is one of the few mono- or di-nuclear bis-pyrazolyl acetate copper complexes [ 81 , 82 ] with uncoordinated acetate moieties, and also one of the relatively not-so-abundant copper complexes showing µ-bridging bromide ions coupled with two pentacyclic N-based ligands [ 83 , 84 , 85 , 86 , 87 , 88 ], described in the CCDC repository [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of furcate substituents R ( tert ‐butyl, phenyl, 2,4,6‐trimethylphenyl), complexes of the composition Cu X 2 L 2 show 1D coordination motif of type B . Moreover, 1‐(furan‐2‐ylmethyl)tetrazole was also reported to generate dinuclear complexes Cu 2 X 4 L 4 of type C . In complexes of types A – C , tetrazoles show N 4 monodentate coordination (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our earlier synthetic and structural investigations of Cu II complexes with tetrazole ligands, [23][24][25][26] in the present work we aimed to design a ligand containing a tetrazolyl moiety that was capable of direct metallation with a copper salt. 1-(5-Amino-3-azapentyl)tetrazole, which has two amino groups that are potentially capable of achieving chelating coordination near the endocyclic carbon atom, was chosen for this purpose.…”
Section: Introductionmentioning
confidence: 99%